Pengujian Perangkat Lunak untuk Aplikasi Sistem Pengelolaan Data Penduduk Berbasis Web di Desa Penarukan, Kecamatan Dusun Utara, Kabupaten Barito Selatan - Angelina Estevani; Cindy Margaretha; Magdalene Isma (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This study examines software testing on a Web-Based Population Data Management System in Penarukan Village. The goal is to ensure system reliability and functionality before implementation. The testing process includes Unit Testing, Integration Testing, Validation Testing, and System Testing. Unit Testing verifies individual functions, Integration Testing ensures module interaction, Validation Testing assesses compliance with user needs, and System Testing evaluates overall system performance. The results confirm that key features such as data management, birth and death registration, and population movement tracking function correctly. Comprehensive testing minimizes errors, making the system stable, secure, and user-oriented.